A model transformation approach for multiscale modeling of software architectures applied to smart cities. (13th June 2021) - Khlif, Ilhem; Hadj Kacem, Mohamed; Eichler, Cédric; Drira, Khalil; Hadj Kacem, Ahmed
Summary: Modeling and specifying correct software systems is a challenging task that can be supported by providing appropriate modeling abstractions. This article proposes an approach for graphical multiscale modeling of such systems using model transformation techniques. The approach is founded on a guided rule‐based iterative modeling process ensuring controlled transition from a coarse‐grained description to a fine‐grained description. It provides also user‐friendly graphical descriptions by extension of UML notations, hence preserving the common practices from software architectures design. The iterative design process is supported by a set of model transformation rules. The rules manage the refinement process (by adding or removing subsystems or by adding or removing details on a given subsystem) as a model transformation. Our approach is supported by a rule‐based generator that implements the automatic transformation of UML diagrams into Event‐B specifications allowing formal verification of their correctness properties, and relieving software architects of mastering formal techniques. To experiment and validate our approach, we consider a case study dedicated to the smart cities.